AKTIVITAS FISIK BERHUBUNGAN DENGAN SINDROM PRAMENSTRUASI PADA REMAJA DI SMA NEGERI 1 AIR PUTIH - Muhammad Syaiful Afiq (Jurnal Psikologi Islam, 2021)
Before menstruation, women usually feel uncomfortable for a short time to a few days, these symptoms can interfere with activities, the symptoms experienced are premenstrual syndrome. Premenstrual syndrome is a condition in women characterized by emotional and physical symptoms that appear in the luteal phase of the menstrual cycle. However, physical activity in the form of exercise can stimulate the release of endorphins and create a calmer feeling when dealing with premenstrual syndrome that is happening. The purpose of this study was to determine the relationship between physical activity and the incidence of premenstrual syndrome in female students at SMA Negeri 1 Air Putih. This type of research uses an analytical research design with a cross sectional study. Consecutive sampling technique was used to determine the size of the sample. Results Based on the data obtained using the chi square method, the p value = 0.033 (p <0.05). Conclusion Based on these results, there is a relationship between physical activity and the incidence of premenstrual syndrome in students of SMA Negeri 1 Air Putih. Keywords : Adolescents, Premenstrual Syndrome, Physical Activity